Depression, anxiety, insomnia, stress, and the way of coping emotions as risk factors for ischemic stroke and their influence on stroke severity: A case–control study in Lebanon - Maalouf, Elise; Hallit, Souheil; Salameh, Pascale; Hosseini, Hassan (Frontiers in Psychiatry, 2023)
Background Stroke is a leading cause of disability and death worldwide. There are numerous debates regarding the relationship between depression, anxiety, insomnia, perceived stress, and ischemic stroke. Moreover, no research on the efficacy of emotion regulation, which is critical for various components of healthy affective and social adaptability, is being conducted. To the best of our knowledge, this is the first study in the MENA region to shed light on the relationship between these conditions and stroke risk, aiming to determine whether depression, anxiety, insomnia, stress, and the way of coping with emotions may be risk factors for ischemic stroke occurrence and to further investigate the ability of two specific types of emotion regulation (cognitive reappraisal and expressive suppression) as possible moderators of the relationship between these psychological diseases and ischemic stroke risk. As a secondary objective, we sought to determine how these pre-existing conditions affect stroke severity levels. Methods This is a case–control survey study involving 113 Lebanese inpatients with a clinical diagnosis of ischemic stroke admitted in hospitals and rehabilitation centers in Beirut and Mount Lebanon, and 451 gender-matched volunteers without clinical signs of stroke as controls recruited from the same hospitals as the cases or attending outpatient clinics for illnesses or treatments unconnected to stroke or transient ischemic attack, as well as visitors or relatives of inpatients (April 2020–April 2021). Data was collected by filling out an anonymous paper-based questionnaire. Results According to the outcomes of the regression model, depression (aOR: 1.232, 95%CI: 1.008–1.506), perceived stress (aOR: 1.690, 95%CI: 1.413–2.022), a lower educational level (aOR: 0.335, 95%CI: 0.011–10.579), and being married (aOR: 3.862, 95%CI: 1.509–9.888) were associated with an increased risk of ischemic stroke. The moderation analysis revealed that expressive suppression had a significant moderating effect on the relationship between depression, anxiety, perceived stress, insomnia, and ischemic stroke risk, resulting in an increased risk of stroke incidence. In contrast, cognitive reappraisal significantly reduced the risk of ischemic stroke by moderating the association between ischemic stroke risk and the following independent variables: perceived stress and insomnia. On the other hand, our multinomial regression model revealed that the odds of moderate to severe/severe stroke were significantly higher in people with pre-stroke depression (aOR: 1.088, 95% CI: 0.747–1.586) and perceived stress (aOR: 2.564, 95% CI: 1.604–4.100) compared to people who had never had a stroke. Conclusion Despite several limitations, the findings of our study suggest that people who are depressed or stressed are more likely to have an ischemic stroke. Consequently, additional research into the causes and effects of depression and perceived stress may provide new directions for preventive strategies that can help reduce the risk of stroke. Since pre-stroke depression and perceived stress were also found to be strongly correlated with stroke severity, future studies should evaluate the association between pre-stroke depression, perceived stress, and stroke severity to gain a deeper understanding of the complex interaction between these variables. Lastly, the study shed new light on the role of emotion regulation in the relationship between depression, anxiety, perceived stress, insomnia, and ischemic stroke.